Thermodynamic and Mechanical Properties of DMPC/Cholesterol Mixed Monolayers at Physiological Conditions - Bañuelos-Frias, Alan; Castañeda-Montiel, Victor Manuel; Alvizo-Paez, Edgar Rogelio; Vazquez-Martinez, Emmanuel Antonio; Gomez, Eduardo; Ruiz-Garcia, Jaime (Frontiers in Physics, 2021)
One of the main known effects of cholesterol is to rigidify the cell membrane throughout the so-called condensing effect. Although many studies have been done in mixtures of cholesterol with different membrane lipids, there are not many studies in a wide concentration range of cholesterol or at physiological conditions. In this work, we studied mixtures of DMPC/Cholesterol monolayers to determine the effect of cholesterol, from very low to physiological concentrations and two pHs. We use a Langmuir balance and Brewster angle microscopy to study their thermodynamic behavior at 37.0 ± 0.1 °C at the air/solution interface. From the analysis of the (π – A) isotherms, we determined the excess area and the compressibility elastic modulus to determine the monolayers mechanical properties. Surprisingly, we found three main effects of cholesterol: The first one is a fluidization effect of the monolayer at all cholesterol concentrations. The second effect is the so-called condensing effect that appears due to the non-ideality of the mixture. The third effect is a stiffness of the monolayer as the cholesterol concentration increases. These effects are stronger in pure water, pH ≈ 6.6, than on buffer at physiological pH = 7.4. We also found that all mixtures are thermodynamically stable at all concentrations at a surface pressure of 30.1 ± 1.6 and 27.4 ± 3.2 mN/m in pure water and buffer, respectively. Furthermore, we compared this stability with a fatty acid monolayer that shows a much lower surface pressure equilibrium value that DMPC or its mixtures with cholesterol, indicating a possibly reason why double chain lipids are better than single chain lipids to made up the cell membrane.